Primary prevention of venous thromboembolism with low molecular weight heparins in surgical patients - 2024: Council of Experts resolution - А. S. Petrikov; Т. V. Vavilova; А. V. Vardanyan; М. N. Zamyatin; I. А. Zolotukhin; К. V. Lobastov; Е. V. Roitman; Е. I. Seliverstov; Yu. М. Stoyko; I. А. Suchkov (IRBIS LLC, 2024)
On March 15, 2024, in Moscow, the Russian Phlebological Association and the National Association of Specialists in Thrombosis, Clinical Hemostasiology and Hemorheology organized a meeting of the Council of Experts during the Russian Forum on Thrombosis and Hemostasis on the acute issues of venous thromboembolism (VTE) primary prevention using low molecular weight heparins (LMWH) in surgical patients with different body weight. The participants reviewed the relevance and prevalence of this problem in surgical practice, discussed risk factors and the frequency of VTE development, including bleeding in the postoperative period, and the Caprini risk score for complications. The discussion also focused on standard and personalized LMWH doses for primary prophylaxis of VTE in the perioperative period in surgical patients, depending on body weight, and the role of laboratory tests, including assessment of LMWH anti-Xa activity for monitoring the efficacy and safety of VTE primary prevention in clinical practice.